Inventário de macrófitas e peixes do quilombo Saco das Almas, Brejo, leste maranhense - PAIVA, Maurício José de Sousa (2024)
This study aimed to conduct a floristic survey of aquatic macrophytes and investigate the ichthyofauna associated with macrophytes in the Comunidade Quilombola Saco das Almas, located in the municipality of Brejo, in the Eastern Maranhão, Brazil. The research was conducted between January and November 2023, with quarterly collections, totaling 99 species of aquatic macrophytes, distributed in 39 families and 63 genera. The highlight was Habenaria repens, a first record for the state of Maranhão. The family Cyperaceae was the richest, with 14 species, followed by Fabaceae (12 spp.) and Melastomataceae (7 spp.). The most common biological forms were amphibious (39 spp.) and emergent (36 spp.). The floristic diversity of the community is remarkable, and the record of H. repens emphasizes the need to expand the study of aquatic macrophytes in Maranhão. Simultaneously, the research investigated the ichthyofauna associated with aquatic macrophytes in 20 streams of the same community. The area is located in the lower Parnaíba River basin, in a Cerrado wetland environment. During the ichthyological survey, 2,125 individuals were captured, distributed in six orders, 25 families, 29 genera, and 61 species, with a highlight for Characiformes. Most of the observed species were associated with aquatic macrophytes, which provide ideal conditions for detritivores and predators, in addition to increasing fish diversity. The research also identified three new records for the Parnaíba River basin, expanding knowledge of the local ichthyofauna. Furthermore, the study presented Echinodorus scaber Rataj as the first record of this species in the state of Maranhão. This new record contributes to understanding the diversity and distribution of the Echinodorus genus in Maranhão. The study emphasizes the importance of aquatic macrophytes for local biodiversity, as these plants are essential for the aquatic ecosystem, serving as habitat and food for various fish species. The research also points to the need to expand studies in little- explored areas of Maranhão, especially in flooded zones, which have great potential for new floristic and faunistic records. Expanding the sampling effort could reveal new species, distribution extensions, and contribute to the conservation of the state’s aquatic ecosystems. In summary, the results of this study indicate a rich diversity of aquatic macrophytes and fish in the Comunidade Quilombola Saco das Almas, and reinforce the importance of continuous research efforts to better understand and conserve the aquatic ecosystems of the region.